Professional Status of Social Work and Social Workers: an Analysis of Public Perception (The Journal of Psychology and Sociology, 2019)
The article is devoted to the analysis of public perception and understanding of social work and social workers, sources of available information about the profession, as well as identifying factors influencing the maintenance of the image of social workers, including factors of the socio-demographic environment that shape the lifestyle, work and consumption.The article presents the results of a quantitative study conducted by the Center for Sociological Research and Social Engineering of the Al-Farabi Kazakh National University in October 2018 among students of the specialty “Social work”. The purpose of the study is to understand and study the image  of social work as one of the new professional activities, the analysis of the leading motives for choosing a profession, self-assessment of personal and professional competencies necessary for social workers, students’ satisfaction with the education they receive, as well as analysis of the existing image, state-   ments and stereotypes.The authors conclude that the profession of social work in Kazakhstan, despite the intensity of its development, faces certain difficulties associated with the process of status professionalization. In addi- tion to the structural problems that exist due to the natural and historical development of social work, such as social solidarity and the maintenance of support traditions, there are restrictive barriers to the development of social work in Kazakhstan.